Immediate Targeted Blood Pressure Reduction Does Not Improve Outcomes in Acute Stroke - Parry, Nicola (MD Conference Express, 2013)
This article presents the final results from the China Antihypertensive Trial in Acute Ischemic Stroke [CATIS; He J et al. JAMA 2013] trial, demonstrating that in acute ischemic stroke patients with elevated blood pressure (BP), antihypertensive treatment to reach a lower target BP does not reduce their risk for death or disability within 14 days.